Pola Keteladanan Guru PAI dalam Membentuk Karakter Peserta Didik - M. Idrus , Mahmudin; Lestari, Anugrah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The main problem in this study is the exemplary pattern of PAI teachers who have not been able to shape the character of students at SMA Negeri 5 Gorontalo Utara, especially religious teachers where students always resist and even presumptuously to refute the teacher, as happened at SMA Negeri 5 Gorontalo Utara, so that through the example of PAI teachers this should shape the character of these students, Somehow now, that's why from this thesis the author describes everything. The purpose of this study was to find out whether the author's expectations about the exemplary pattern of PAI teachers could shape the character of students at SMA Negeri 5 Gorontalo Utara. This type of research is classified as qualitative research. This research is classified as a type of field research and includes pure research or Ipure research. Data collection techniques use observation and interview methods, while data analysis techniques used are collecting, sorting, clarifying, synthesizing, making an overview, and making an index. This study used triangulation of data sources. Based on the results of qualitative research conducted, the end of this study shows that from the above problems now the pattern of example of PAI teachers has been able to shape the character of students even though there are still few students who are not willing to emulate PAI teachers at SMA Negeri 5 Gorontalo Utara, so it can be concluded that the pattern of example of PAI teachers at SMA Negeri 5 Gorontalo Utara is good enough.